Modern Approaches to Personnel Management in Secondary Educational Institutions (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
The article discusses various approaches and principles of general education school management. The tasks of a modern school educational institution are characterized, the influence of the head and his competence on the positive impact on the effectiveness of the management of the educational institution are outlined in the school.